An Assessment the Efficiency for A Parabolic Trough Solar Collector with Different Horizontal Axis by Using Tracking System - Ali A. F. Al- Hamadani (Diyala Journal of Engineering Sciences, 2017)
The solar energy in Iraq is available, but till now a little application for using it. The parabolic trough solar collector (PTSC) technology, which considers being one of the low-cost and most operative technologies for solar power plant. The performance of a PTSC with solar tracking system has been experimentally investigated under Kut city, Iraqi climate conditions. The experimental work focused on changing the horizontal axis and mass flow rate of water. It has been started with 0o, 30o, 60o receptively. The zero angle represents an east direction, then rotate toward the south. The instantaneous efficiency was employed to evaluate the thermal performance of the PTSC. The equation had been solved using equation engineering solver (EES). The results showed that Kut city holds a good potential for such energy generation technology with an average efficiency of 38.8% and instantaneous efficiency that can reach as high as 70%. This study is highly encouraging the Iraq government to invest in the PTSC technology in Iraq to meet the increasing demand on electric power. The best efficiency is zero angle which represents the east direction. The efficiency, enhanced with the mass flow rate till certain value. The heat transfer coefficient for zero angle was significant compare with other angles. The result was validated with fixed parabolic trough and a good agreement. The performance improved with increase the mass flow rate till 30 kg/hr after that no any effect of it.